Intrapartum Fetal and Maternal Complications in Low-Risk Pregnancy: Experience of a Tertiary Hospital in Low-Income Countries - Alsammani, Mohamed Alkhatim (Open Access Maced J Med Sci, 2019)
AIM: To determine the frequencies of intrapartum fetal and maternal complications in women without the identified prenatal risk factor METHODS: We conducted a prospective cross-sectional investigation from January to June 2017 at Khartoum North Maternity Hospital in women categorised pregnancies as low risk (no prenatal risk factors). We evaluated adverse intrapartum fetal and maternal outcomes. RESULTS: Among 600 pregnancies, of these, 12.5% (n = 75) developed fetal or / and maternal complications. The Frequency of primary cesarean delivery, forceps, and ventose among low-risk pregnancies in this study were 16%, 3%, and 2% respectively. Other adverse pregnancy outcomes were PPH (5%), Blood transfusion (4.5%), admission to ICU (1.8%), while perineal tear, cesarean hysterectomy, and re-laparotomy have equal weight (0.3%). Among all births, the most common adverse fetal outcomes were birth asphyxia (3.8%), low birth weight (2%), admission to the neonatal intensive care unit (1.8%), and fresh stillborn babies (1.3%). CONCLUSION: Of all low-risk pregnancies, 12.5% were reported to have serious obstetrics and neonatal complications. This information is essential for evaluating resources in delivery centres and hospitals and to provide equipment and further training of medical personnel to provide optimal quality care and patient safety.